Productivity of Zero-Tilled Dibbled Sunflower under Different Planting Densities in Salt Affected Soils of Bangladesh: Productivity of Zero-Tilled Sunflower in Salt-Affected Soils - Rashid, Md Harunur Rashid; Goswami, Palash Chandra; Raisa, Tasfia Tabassum (SAARC Journal of Agriculture, 2025)
The growth and yield of sunflowers is affected by salinity. Planting density is an important factor for enhancing the productivity and profitability of sunflowers in saline ecosystems which has not been sufficiently evaluated in farmers' fields of diverse saline soils. An on-farm experiment was conducted in three salt-affected sites with three planting densities, 29630, 37037, and 74074 ha-1 through the planting arrangement of 75 cm × 45 cm, 60 cm × 45 cm, and 45 cm × 30 cm, respectively, under zero tilled condition with four replications. Results revealed that seed yield obtained in planting arrangement, 60 cm × 45 cm and 45 cm × 30 cm were 31.3 % and 22.2 % higher than 75 cm × 45 cm, respectively. The locations with salinity of 6.02 and 7.71 dS m-1 decreased seed yield by 6.5 % and 17.4 %, respectively, compared to 4.93 dS m-1. The planting arrangement, 60 cm × 45 cm increased the gross margin by 35-50 % but decreased by 24-49 % in 45 cm × 30 cm. The adoption of a planting arrangement, 60 cm × 45 cm can increase the productivity of zero-tilled dibbled sunflower and thus increase the income of coastal saline farmers. SAARC J. Agric., 22(2): 67-79 (2024)